Rancang Bangun Trainer Spectrum Analyzer berbasis Raspberry Phyton dan Register Transfer Level - Software Defined Radio - Sabur, Fatmawati; Sinaga, Ucok (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
Spectrum Analyzer is a device that is reliable enough to analyze or test the condition of a system in a communication network. However, the high purchase price of a Spectrum Analyzer means that not everyone can afford it. One solution to overcome this problem is to make a piece of hardware capable of performing the same performance as a Spectrum Analyzer but at a relatively cheaper price. Prototype Spectrum Analyzer to be implemented is a device capable of displaying the spectrum of a signal in a certain frequency range. This engineering was carried out from July to October 2020 at the Makassar Aviation Polytechnic Campus and testing tools with a comparison tool was carried out at Otban Region V Makassar. The technique or method used in data collection is the library method by collecting some written data from books, literature, and tutorials on the internet, as reference material and then analyzing solutions that can be taken in solving problems. From the results of tests carried out by using RTL-SDR on the Single Board Computer (SBC), Raspberry pi can display the frequency spectrum whether it is done singly or applied to the network so that it can be used as a learning medium for wireless technology practice or other materials that measure frequency from sergi, the performance of the trainer spectrum analyzer with the use of raspberry pi as a device for processing radio / wireless signals is quite good at utilization with CLI mode (command line interface) but is relatively slow when used on the desktop as a portable spectrum analyzer that can be used as a learning medium.